Diagnostic value of plasma NGAL and intraoperative diuresis for AKI after major gynecological surgery in patients treated within an intraoperative goal-directed hemodynamic algorithm: A substudy of a randomized controlled trial. Issue 28 (July 2017) - Hunsicker, Oliver; Feldheiser, Aarne; Weimann, Andreas; Liehre, David; Sehouli, Jalid; Wernecke, Klaus-Dieter; Spies, Claudia
Abstract : Abstract: Data on early markers for acute kidney injury (AKI) after noncardiovascular surgery are still limited. This study aimed to determine the diagnostic value of plasma neutrophil-gelatinase-associated lipocalin (pNGAL) and intraoperative diuresis for AKI in patients undergoing major abdominal surgery treated within a goal-directed hemodynamic algorithm. This study is a post-hoc analysis of a randomized controlled pilot trial comparing intravenous solutions within a hemodynamic goal-directed algorithm based on the esophageal Doppler in patients undergoing epithelial ovarian cancer surgery. The diagnostic value of plasma NGAL obtained at ICU admission and intraoperative diuresis was determined with respect to patients already meeting AKI criteria 6 hours after surgery (AKI6h ) and to all patients meeting AKI criteria at least once during the postoperative course (AKItotal ). AKI was diagnosed by the definition of the Kidney Disease Improving Global Outcome (KDIGO) group creatinine criteria and was screened up to postoperative day 3. Receiver operating characteristic curves including a gray zone approach were performed. A total of 48 patients were analyzed. None of the patients had increased creatinine levels before surgery and 14 patients (29.2%) developed AKI after surgery. Plasma NGAL was predictive for AKI6h (AUCAKI6h 0.832 (95% confidence interval [CI], 0.629–0.976), P  = .001) and AKItotal (AUCAKItotal 0.710 (CI 0.511–0.878), P  = .023). The gray zones of pNGAL calculated for AKI6h and AKItotal were 210 to 245 and 207 to 274 ng mL −1, respectively. The lower cutoffs of the gray zone at 207 and 210 ng mL −1 had a negative predictive value (NPV) (i.e., no AKI during the postoperative course) of 96.8% (CI 90–100) and 87.1% (CI 78–97), respectively. Intraoperative diuresis was also predictive for AKI6h (AUCAKI6h 0.742 (CI 0.581–0.871), P  = .019) with a gray zone of 0.5 to 2.0 mL kg −1 h −1 . At the lower cutoff of the gray zone at 0.5 mL kg −1 h −1, corresponding to the oliguric threshold, the NPV was 84.2% (78–92). This study indicates that pNGAL can be used as an early marker to rule out AKI occurring within 3 days after major abdominal surgery. Intraoperative diuresis can be used to rule out AKI occurring up to 6 hours after surgery. Trial Registration: ISRCTN 53154834. Abstract : Supplemental Digital Content is available in the text